1996
DOI: 10.2527/1996.7461349x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzyme preparations on in situ and in vitro degradation and in vivo digestive characteristics of mature cool-season grass forage in beef steers.

Abstract: In situ and in vitro studies with a 3 x 2 x 5 factorial arrangement of treatments with an added untreated control evaluated three enzyme preparations, two levels of enzyme, and five moisture conditions of grass forage. Enzyme preparations predominantly contained cellulase and xylanase and will be designated as enzyme 1 (E1), enzyme 2 (E2), and a 50:50 combination of E1 and E2 (E1E2). The five moisture conditions included fresh, wilted, dried and rehydrated to fresh, dried and rehydrated to wilt, and dried gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
93
4
30

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 15 publications
(17 reference statements)
20
93
4
30
Order By: Relevance
“…Numerous studies have reported increased digestion of DM and fibre measured in situ or in vitro (Nakashima et al 1988;Feng et al 1996;Hristov et al 1996;Yang et al 1999;Colombatto 2000;Colombatto et al 2002) or in vivo (Feng et al 1996;Krause et al 1998;Yang et al 1999;Beauchemin et al 2000;Kung et al 2000). These increases in feed digestion are somewhat unexpected given the exceptionally high starch and fibre digesting capacity of the rumen.…”
Section: Mode Of Actionmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies have reported increased digestion of DM and fibre measured in situ or in vitro (Nakashima et al 1988;Feng et al 1996;Hristov et al 1996;Yang et al 1999;Colombatto 2000;Colombatto et al 2002) or in vivo (Feng et al 1996;Krause et al 1998;Yang et al 1999;Beauchemin et al 2000;Kung et al 2000). These increases in feed digestion are somewhat unexpected given the exceptionally high starch and fibre digesting capacity of the rumen.…”
Section: Mode Of Actionmentioning
confidence: 98%
“…Various studies have shown that exogenous enzymes enhanced rate of in situ or in vitro digestion measured using short-term incubations (Nakashima et al 1988;Feng et al 1996;Hristov et al 1996;Yang et al 1999;Colombatto 2000;Colombatto et al 2002). However, most studies have not found exogenous enzymes to improve the extent of in situ or in vitro digestion (Nakashima et al 1988;Feng et al 1996;Hristov et al 1996;Iwaasa et al 1999;Yang et al 1999;Colombatto 2000).…”
Section: Direct Hydrolysismentioning
confidence: 99%
“…Thus, some studies conducted by Luchini et al [18], Feng et al [8] and Wilman et al [39] propose in vitro methods for determining ruminal feed degradation because of a greater speed and lower expense than in vivo and in situ methods.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, enzymes are assayed at their optimum pH or temperature (Wood and Bhat 1988), which are generally a pH range of 4.5 to 5.5 and a temperature range of 45 to 60°C. However, in most of the published reports on enzymes as feed additives for ruminants, the experimental conditions used in the assays to determine enzyme activities were not stated Feng et al 1996;Lewis et al 1996). Furthermore, where assay conditions were stated, they rarely resemble the in vivo situations.…”
Section: Temperature and Phmentioning
confidence: 99%